Civil War - Blattman, Christopher; Miguel, Edward (Journal of Economic Literature, 2010)
Most nations have experienced an internal armed conflict since 1960. Yet while civil war is central to many nations' development, it has stood at the periphery of economics research and teaching. The past decade has witnessed a long overdue explosion of research into war's causes and consequences. We summarize progress, identify weaknesses, and chart a path forward. Why war? Existing theory is provocative but incomplete, omitting advances in behavioral economics and making little progress in key areas, like why armed groups form and cohere, or how more than two armed sides compete. Empirical work finds that low per capita incomes and slow economic growth are both robustly linked to civil war. Yet there is little consensus on the most effective policies to avert conflicts or promote postwar recovery. Cross-country analysis of war will benefit from more attention to causal identification and stronger links to theory. We argue that micro-level analysis and case studies are also crucial to decipher war's causes, conduct, and consequences. We bring a growth theoretic approach to the study of conflict consequences to highlight areas for research, most of all the study of war's impact on institutions. We conclude with a plea for new and better data. (JEL D72, D74, O17)